Human Rhabdomyosarcoma Cell Lines for Rhabdomyosarcoma Research: Utility and Pitfalls - Hinson, Ashley R.; Jones, Rosanne; Crose, Lisa E.; Belyea, Brian; Barr, Frederic G.; Linardic, Corinne M. (Frontiers in Oncology, 2013)
Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of childhood and adolescence. Despite intergroup clinical trials conducted in Europe and North America, outcomes for high risk patients with this disease have not significantly improved in the last several decades, and survival of metastatic or relapsed disease remains extremely poor. Accrual into new clinical trials is slow and difficult, so in vitro cell line research and in vivo xenograft models present an attractive alternative for preclinical research for this cancer type. Currently, 30 commonly used human RMS cell lines exist, with differing origins, karyotypes, histologies, and methods of validation. Selecting an appropriate cell line for RMS research has important implications for outcomes. There are also potential pitfalls in using certain cell lines including contamination with murine stromal cells, cross-contamination between cell lines, discordance between the cell line and its associated original tumor, imposter cell lines, and nomenclature errors that result in the circulation of two or more presumed unique cell lines that are actually from the same origin. These pitfalls can be avoided by testing for species-specific isoenzymes, microarray analysis, assays for subtype-specific fusion products, and short tandem repeat analysis.